Consumer food demand in Japan before and after the beginning of COVID-19: AIDS analysis using home scan data - Ito, Nobuhiro; Maruyama, Yuki; Wakamatsu, Hiroki (Frontiers in Sustainable Cities, 2022)
COVID-19 had an impact not only on human health but also on consumers' food consumption. Employing the Almost Ideal Demand System (AIDS), this study analyzes whether consumers change their demand for food between 2019 and 2020 in Japan, where the legal action was not implemented to restrict consumer behavior. Using the home scan data, 25 food items, including eating out and delivery, were analyzed to see the impact of COVID-19. Results show that the increase in shares of expenditure is mainly related to consumption in the home in 2020, while that for eating out turned into a significant decrease. The estimated own price elasticity and expenditure elasticity of demand shows that ingredients for home cooking are more substitutive with eating out and more complementary within the ingredients in 2020.